2020
DOI: 10.1111/jerd.12589
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable fiberglass post after 3D guided endodontic treatment: Novel approaches in restorative dentistry

Abstract: Objective: The rehabilitation of extensively damaged teeth with great structural loss and calcified root canals represents a challenge for dentistry. Classically, this restorative procedure of endodontically treated teeth involves intraradicular post placement.Retentive function post that can closely adapt to the root canal without the excessive wear of intraradicular dentin has a fundamental importance to ensure the longevity of the restoration.Clinical considerations: This report presents a clinical case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ]. In twenty-five of them, GE was used for the treatment of pulp obliteration [ 3 , 9 , 35 , 36 , 37 , 38 , 39 ,…”
Section: Resultsmentioning
confidence: 99%
“…From the 37 selected case reports ( Table 2 ), 25 of them had at least one year of follow-up with excellent results in terms of the absence of symptomatology or evidence of bone regeneration [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Eighteen of them were performed with only single-rooted teeth [ 3 , 9 , 38 , 40 , 44 , 46 , 50 , 51 , 52 , 53 , 55 , 58 , 60 , 61 , 62 , 63 , 64 , 65 ]. In twenty-five of them, GE was used for the treatment of pulp obliteration [ 3 , 9 , 35 , 36 , 37 , 38 , 39 ,…”
Section: Resultsmentioning
confidence: 99%
“…All the studies produced flaps analogous to those employed in clinical settings of endodontic microsurgery. Several studies have suggested avoiding the flap procedure when removing the masticatory palatal mucosa [64]. This novel approach to endodontic microsurgery may lessen the risk of complications and post-operative discomfort when apicoectomies on the palatal roots of maxillary molars are performed [66].…”
Section: Openings Used In Endodonticsmentioning
confidence: 99%